Combined Performance of Polyethylene Terephthalate Waste Plastic Polymer and Crumb Rubber in Modifying Properties of Hot Mix Asphalt - Alemu, Getnet Mekuria; Melese, Damtew Tsige; Mahdi, Teyba Wedajo; Negesa, Adamu Beyene (Advances in materials science and engineering, 2023)
Nowadays, the use of recycled waste materials in road pavement is regarded not only as a positive option in terms of sustainability but also as an appealing option in terms of providing improved service performance. The current study aimed at evaluating the performance of crumb rubber and polyethylene terephthalate plastic polymer in asphalt mixture in modifying the mechanical properties of asphalt pavement. Experimental tests were carried out both for asphalt binder and asphalt mixture. Different proportions of mix for crumb rubber and polyethylene terephthalate plastic polymer were used to systematically investigate the effect of mix ratio on performance of the asphalt material. The experimental analysis reveals that the combined application of 10% by weight of crumb rubber chips and 2% polyethylene terephthalate plastic polymer are the ideal mix ratios found effective in modifying properties of the asphalt mixture. The asphalt binder test results indicate that adding 10% crumb rubber to asphalt binder reduced penetration by 1.56% along with increment of the softening point by 4.33%. Furthermore, the indicated optimum mix amount resulted in 0.17% rise, 20.07% drop, and 20.71% increase in Marshal stability, flow, and stiffness, respectively. Besides, tensile strength of the asphalt mixture was enhanced with addition of the filler and binder materials. It was witnessed that the combined application of the additives performs better than their separate use in modifying properties of the asphalt mix.